Using software as a service to support the academic activities of students in higher education institutions with a relative lack of resources - Akande, Akinlolu Olumide (Department of Information Systems, 2019)
The contribution of Software as a Service (SaaS) towards improved access to software, cost reduction, better quality of learning and enhanced communication and collaboration in higher education institutions (HEIs) cannot be over emphasised. Some HEIs are faced with issues such as tight budget, lack of needed software, inadequate human resources and lack of adequate infrastructure. This research refers to such HEIs as those with a relative lack of resources because the resources intended for a single student are often shared among ten or more students. Hence many students are unable to cope with their academic activities and some end up failing or even dropping out. Finding alternative ways to provide the necessary software for students is therefore a priority for HEIs with a relative lack of resources. SaaS offers a possible alternative for them and it is gaining their attention. The goal of this research was to empower HEIs, their students, lecturers and Information Technology (IT) staff by providing them with a better understanding of SaaS and to provide them with a tool to manage the adoption and implementation of SaaS. Also, the intention was to make practical, theoretical and methodological contributions to the scientific body of knowledge in the area of Software as a Service. To achieve the goals, this research investigated the use of SaaS in HEIs with a relative lack of resources and found SaaS to be effective in providing wider access to software for students in HEIs with a relative lack of resources. This research also identified benefits and limitations of SaaS and how SaaS can help in addressing the barriers to learning and contribute towards the creation of a conducive learning environment for students. The different SaaS offerings available for education and the issues and contradictions associated with the use of SaaS in HEIs were also identified. Furthermore, a set of propositions and an integrated framework were developed using the data from the literature, books, institutional documents and interview data. Although HEIs are continuously introducing SaaS offerings into their academic activities and SaaS promises to improve the learning experience of students in HEIs by improving access to software, improving the sharing of documents and files, improving collaboration as well as communication, this research found that the use of SaaS by students in HEIs is still relatively low and uncovered the reasons for this. The HEIs in Nigeria and South Africa were used as exemplars and the problems they face with regards to resource availability were identified using the activity theory (AT) as a theoretical lens. The Astin’s IEO model and the Students involvement theory were also used to explain some issues relating to the importance of student participation in academic activities involving the use of SaaS. Although the study was focused on students, data from lecturers and IT staff was used for triangulation to increase the credibility and validity of the data obtained from the students. This research found that students believe that SaaS can improve their learning experience and there is an unwavering support for the campus wide implementation of SaaS among students. In the Nigerian HEIs, software piracy was found to be a major problem as students cannot afford to buy the original software needed for academic activities. Another major finding from the Nigerian HEIs is the rampant claims that corruption affects the implementation of SaaS and other ICT initiatives as funds meant for implementation are often diverted for personal gains. In both Nigeria and South Africa, this research found that there is limited or no internet access in some areas and the students who come from such areas are unable to access SaaS from home. This limits their ability to enjoy the anytime, anywhere access advantage of SaaS. This research concluded by suggesting the need for the government and education institutions to provide training for learners and encourage them to be computer literate from an early stage as this could improve their confidence in using technologies such as SaaS when they get to higher education level.